2014
DOI: 10.1159/000369452
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Pulposus Mesenchymal Stem Cells in Acidic Conditions Mimicking Degenerative Intervertebral Discs Give Better Performance than Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: The microenvironment of the intervertebral disc (IVD) is characterized by matrix acidity, hypoxia, hyperosmolarity and limited nutrition, which are major obstacles to stem cell-based regeneration. Our recent work showed that nucleus pulposus mesenchymal stem cells (NPMSCs) had advantages over traditional sources of cell therapy under IVD-like hypoxic and hyperosmotic conditions. Here, we examined the viability, proliferation and matrix metabolism of NPMSCs compared with adipose tissue-derived mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 37 publications
4
76
0
Order By: Relevance
“…Certain studies have reported that these stem cells lack viability, proliferation and matrix biosynthesis under conditions resembling the IVD microenvironment, which negatively influences the biological and metabolic vitality of stem cells and impairs their repair potential (16,17). In recent years, increasing evidence supported the existence of nucleus pulposus MSCs (NPMSCs) in the nucleus pulposus (18)(19)(20)(21)(22)(23)(24). They possess a similar capacity of chondrogenic differentiation to that of BMSCs (18) and have better adaptability to the harsh IVD microenvironment than ADMSCs (24).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain studies have reported that these stem cells lack viability, proliferation and matrix biosynthesis under conditions resembling the IVD microenvironment, which negatively influences the biological and metabolic vitality of stem cells and impairs their repair potential (16,17). In recent years, increasing evidence supported the existence of nucleus pulposus MSCs (NPMSCs) in the nucleus pulposus (18)(19)(20)(21)(22)(23)(24). They possess a similar capacity of chondrogenic differentiation to that of BMSCs (18) and have better adaptability to the harsh IVD microenvironment than ADMSCs (24).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing evidence supported the existence of nucleus pulposus MSCs (NPMSCs) in the nucleus pulposus (18)(19)(20)(21)(22)(23)(24). They possess a similar capacity of chondrogenic differentiation to that of BMSCs (18) and have better adaptability to the harsh IVD microenvironment than ADMSCs (24). This suggests that NPMSCs may be a good candidate cell for IVD regeneration by cell therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies [Li et al, 2013;Han et al, 2014] and many others [Blanco et al, 2010;Wu et al, 2017;Molinos et al, 2018] have demonstrated that the IVD itself contains MSCs. Blanco et al [2010] identified human NP-derived (NP)-MSCs from human degenerative discs, and found that these cells fulfilled nearly all the morphological, immunophenotypical, and differentiation criteria described by the International Society of Cell Therapy for MSCs.…”
mentioning
confidence: 99%
“…NPPCs, a newly discovered type of endogenous intervertebral disc (IVD) SCs, have been characterized in mouse, rabbit, porcine, canine, rhesus monkey and both healthy and degenerating human IVDs [6][7][8][9][10]. In clinical practice, spine surgery patients treated with a dynamic fixation system occasionally display regeneration phenomena in operated segments [11], while experimentally, NPPCs exhibit superior performance in surviving adverse environments [12][13][14]. However, recent reports have indicated that NPPCs gradually become exhausted with increased age and progressive degeneration in IDD [15][16][17].…”
Section: Introductionmentioning
confidence: 99%